ANALISIS PENGARUH BAURAN PEMASARAN RITEL TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN BERBELANJA DI GIANT HYPERMARKET KOTA PEKANBARU (Jurnal Tepak Manajemen Bisnis, 2014)
This research is to investtigate the influence of merchandise, price, place, promotion, Atmospher, and retail sevice effect on cutomer statisfaction and costumer loyalty. The reserach was done in Pekanbaru in January untilNovember 2013. Samples of this reserach were the Pekanbaruâs citizen and household needs. Convience sampling became theresearchâ choice in sampling method. 250 customer of Giant Hypermarket Pekanbaru was taken as sample. Data analysis technique of path analysis.The results ofthis study indicatethat Merchandise, price, place, Promotion, Atmospher, Retail service indicatesthat had positive influence. Ifthe higher Merchandise, price, Location, Promotion, Atmospheric, Retail service, the customer statisfaction is also getting strongerandthroughthecustomersatisfactionvariableswill directlyincreasecustomer loyalty. Price and promotion variables showed the most dominant influence than other variablesKeywords: RetailMarketing Mix, CustomerSatisfactionandLoyalty.